Azot i jego frakcje w komunalnych osadach ściekowych = Nitrogen and its fractions in municipal sawage sludge - Czekała, Jacek (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The paper presents the results of research on the share of nitrogen fractions in household sewage sludge. It was found that on average 41.8% to 52.4% of nitrogen in sludge underwent hydrolysis. Yet, it should be stressed that 14.4% to 21.3% of the total amount of nitrogen included bonds characterised by water-soluble fractions, and thus easily accessed by plants.
Keywords: osady ściekowe; frakcje azotu; sewage sludge; nitrogen fractions